The potential use of lactate blockers for the prevention of COVID-19 worst outcome, insights from exercise immunology. (March 2021) - AbdelMassih, Antoine Fakhry; Menshawey, Rahma; Hozaien, Rafeef; Kamel, Aya; Mishriky, Fady; Husseiny, Reem J.; Hanoura, Aia Mohamed; Yacoub, Elaria; AlShehry, Nada; Menshawey, Esraa; El-Husseiny, Nadine; Yasser, Reem; et al.
Abstract: Following the decline in Physical Activity (PA) due to COVID-19 restrictions in the form of government mandated lockdowns and closures of public spaces, the modulatory effect of physical exercise on immunity is being heavily revisited. In an attempt to comprehend the wide discrepancy in patient response to COVID-19 and the factors that potentially modulate it, we summarize the findings relating PA to inflammation and immunity. A distinction is drawn between moderate intensity and high intensity physical exercise based on the high lactate production observed in the latter. We hypothesize that, the lactate production associated with high intensity anaerobic exercise is implicated in the modulation of several components of the innate and adaptive immunity. In this review, we also summarize these immunomodulatory effects of lactate. These include increasing serum IL-6 levels, the main mediator of cytokine storms, as well as affecting NK cells, Macrophages, Dendritic cells and cytotoxic T-lymphocytes. The implications of high lactate levels in athletic performance are highlighted where athletes should undergo endurance training to increase VO2 max and minimize lactate production. Tumor models of hypoxia were also reported where lactate levels are elevated leading to increased invasiveness and angiogenesis. Accordingly, the novel lactate blocking strategy employed in cancer treatment is evaluated for its potential benefit in COVID-19 in addition to the readily available beta-blockers as an antagonist to lactate. Finally, we suggest the diagnostic/prognostic purpose of the elevated lactate levels that can be determined through sweat lactate testing. It is the detrimental effect of lactate on immunity and its presence in sweat that qualify it to be used as a potential non-invasive marker of poor COVID-19 outcome.